Bevacizumab-Induced Reversible Thrombocytopenia in a Patient with Adenocarcinoma of Colon: Rare Adverse Effect of Bevacizumab - Jeevan Kumar; Manorama Bhargava; Shyam Aggarwal (Case Reports in Oncological Medicine)
We report a case of bevacizumab- (BEV-) induced thrombocytopenia in a 59-year-old man with adenocarcinoma of colon. After colectomy, the patient was treated with twelve cycles of FOLFOX-4 (folinic acid, 5-fluorouracil, and oxaliplatin) regimen. On relapse, he was treated with FOLFIRI (folinic acid, 5-fluorouracil, and irinotecan) regimen along with BEV 10 mg/kg for 6 cycles. After that, BEV was continued for maintenance as a single agent at an interval of three weeks. After the13th cycle of BEV, the patient developed melena with epistaxis and thrombocytopenia, from which he recovered on withdrawal of BEV. On rechallenge with half the initial dose, there was once again a reversible drop in platelet count. The proposed mechanism of thrombocytopenia may be immune-mediated peripheral destruction of platelets.